2021
DOI: 10.1186/s13030-021-00218-x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective cognitive impairment and presenteeism mediate the associations of rumination with subjective well-being and ill-being in Japanese adult workers from the community

Abstract: Background In recent years, the roles of rumination, subjective cognitive impairment (SCI), and presenteeism have been emphasized in occupational mental health. However, associations between rumination, SCI, presenteeism, and psychological well-being are not fully understood. We hypothesized that SCI and presenteeism mediate the associations between rumination and subjective well-being (SWB) and subjective ill-being (SIB). Hence, we investigated the mediating roles of SCI and presenteeism in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In addition, Mann and Holdsworth (2003) concluded that when a person teleworking, they will also have presenteeism, making them work for a longer time and keep working even though they are sick since they are trying to maintain the trust of their superiors. Based on the research findings by (Toyoshima et al, 2021;Heitor et al, 2021), presenteeism has a negative relationship with psychological well-being. Mostafa (2021), in a study, revealed an effect of teleworking on physiological well-being during the COVID-19 pandemic.…”
Section: The Relationship Between Teleworking and Psychological Well-...mentioning
confidence: 99%
“…In addition, Mann and Holdsworth (2003) concluded that when a person teleworking, they will also have presenteeism, making them work for a longer time and keep working even though they are sick since they are trying to maintain the trust of their superiors. Based on the research findings by (Toyoshima et al, 2021;Heitor et al, 2021), presenteeism has a negative relationship with psychological well-being. Mostafa (2021), in a study, revealed an effect of teleworking on physiological well-being during the COVID-19 pandemic.…”
Section: The Relationship Between Teleworking and Psychological Well-...mentioning
confidence: 99%
“…In a previous Japanese study, CCs mediated the influence of insomnia and anxiety on loss of work productivity [ 25 ]. Additionally, a recent study suggested that the loss of work productivity mediates the influence of CCs on SWB and SIB in Japanese adult workers [ 41 ]. Therefore, sleep disturbance and anxiety might lead to poorer CCs, and CCs might decrease work productivity, and consequently, SWB and SIB might be exacerbated in Japanese workers.…”
Section: Discussionmentioning
confidence: 99%
“…Such programs have 2 demonstrated the ability to improve employee physical activity, cardiovascular and musculoskeletal disease risk, respiratory function and body composition [4]. These programs are also proposed to enhance cognition, an additional component of wellbeing [4,5]. Specifically, cognition is critical to all voluntary actions, including occupational success and functional independence [6].…”
Section: Introductionmentioning
confidence: 99%
“…Improved cognition and other associated benefits of exercise can also benefit workplace productivity [ 6 , 8 ] . H o w e v e r , m o r e r e s e a r c h i s n e e d e d t o e v aluate the relationship between exercise with productivity and cognitive outcomes to optimise the implementation of workplace wellness programs for employees and corporations [5,9].…”
Section: Introductionmentioning
confidence: 99%